2020
DOI: 10.18778/1733-8077.16.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Other-Than-Human Identity: A Narrative Approach to Otherkin, Therianthropes, and Vampires

Abstract: Drawing on in-depth, narrative interviews with 24 self-identified Otherkin, Therianthropes, and Vampires, we explore how members of these communities navigate Bamberg’s three “dilemmatic spaces” or tensions of continuity/change, similarity/difference, and person-to-world/world-to-person fit. With regard to the first, we identify four aetiological narratives (walk-ins, reincarnation, trapped soul, and evolutionary soul), and discuss stories of shifts and awakening. For the second, we discuss how participants ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Clegg et al (2019) also investigated the mental health and well-being of people who identify as therians, finding that while therians tended to score lower than nontherian respondents on measures of positive social relationships, therian identity also appeared to serve as a protective factor for those scoring higher on measures of autism and schizotypy. Baldwin and Ripley (2020) examined the development of identity among spiritually oriented therians, otherkin, and those who identify as vampires, drawing on 24 interviews to show how members of these communities use common narrative strategies to construct their identities. They found that, while the therians, otherkin, and vampire-identified informants they interviewed were attempting to place their identity into a coherent story in similar ways to those with "more standard identities," they were "doing so with far fewer narrative resources" (p. 9).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Clegg et al (2019) also investigated the mental health and well-being of people who identify as therians, finding that while therians tended to score lower than nontherian respondents on measures of positive social relationships, therian identity also appeared to serve as a protective factor for those scoring higher on measures of autism and schizotypy. Baldwin and Ripley (2020) examined the development of identity among spiritually oriented therians, otherkin, and those who identify as vampires, drawing on 24 interviews to show how members of these communities use common narrative strategies to construct their identities. They found that, while the therians, otherkin, and vampire-identified informants they interviewed were attempting to place their identity into a coherent story in similar ways to those with "more standard identities," they were "doing so with far fewer narrative resources" (p. 9).…”
mentioning
confidence: 99%
“…Instead, they identify as a species of non-human animal that either currently exists or has existed and is now extinct” and an otherkin as a person “[identifying] as a nonhuman being that is typically considered mythical or fantasy-based (e.g., fairy, elf, unicorn).” The terms therianthropy and otherkinship refer to the lived experience of therians and otherkin; theriotype and kintype refer to the type of nonhuman animal or mythical creature as which they identify. Research on this experience is scarce, and previous studies have focused on identity formation (Grivell et al, 2014) and on the ways therians and otherkin draw on collective linguistic resources to make sense of their experience (Baldwin & Ripley, 2020; Proctor, 2018). This article contributes to the literature on this relatively unstudied phenomenon by drawing upon both phenomenology and integrated psychoanalytic theories of development to describe the lived experience of therianthropy and otherkinship and formulate an understanding of how the environment (natural and manmade) and the social milieu (social space, relationships, etc.)…”
mentioning
confidence: 99%
See 1 more Smart Citation